Participatory Democracy and the Legal Politics of Local Legislation: The Constitutional Role of Regional Legislatures in Adaptive and Responsive Governance - Ramdin Ramdin; Taufik Firmanto (Fakultas Syariah IAIN Langsa, 2026)
Ideally, participatory democracy positions citizens as active subjects in the formation of regional regulations through the representative role of the Regional People’s Representative Council (DPRD) as a local legislative body. In practice, however, public participation in regional law-making remains largely procedural, elitist, and insufficiently influential on the substantive orientation of regional legal politics. This condition creates a gap between the normative ideals of local democracy and the empirical reality of adaptive and responsive local governance. This study aims to analyze the constitutional role of the DPRD within the political framework of regional legislation and to assess the extent to which the institutionalization of public participation contributes to the quality of regional regulations. This article employs normative legal research using a qualitative approach, combining the statute approach and the conceptual approach. The data are derived from primary and secondary legal materials and analyzed through descriptive-analytical methods. The findings demonstrate that strengthening the deliberative function of the DPRD and embedding substantive public participation mechanisms are essential to producing legitimate, adaptive, and socially responsive regional legislation in a dynamic democratic context.